Yarsagumba is a Promising Therapeutic Option for Treatment of Pulmonary Hypertension due to the Potent Anti-Proliferative and Vasorelaxant Properties - Himal Luitel; Tatyana Novoyatleva; Akylbek Sydykov; Aleksandar Petrovic; Argen Mamazhakypov; Bhuminand Devkota; Malgorzata Wygrecka; Hossein Ardeschir Ghofrani; Sergey Avdeev; Ralph Theo Schermuly; Djuro Kosanovic (Medicina, 2020)
Background and objectives: Pulmonary hypertension (PH) is characterized by the vasoconstriction and abnormally proliferative vascular cells. The available allopathic treatment options for PH are still not able to cure the disease. Alternative medicine is becoming popular and drawing the attention of the general public and scientific communities. The entomogenous fungus Yarsagumba (Cordyceps sinensis) and its biologically active ingredient cordycepin may represent the therapeutic option for this incurable disease, owing to their anti-inflammatory, vasodilatory and anti-oxidative effects. Methods: In this study, we investigated whether Yarsagumba extract and cordycepin possess anti-proliferative and vasorelaxant properties in the context of PH, using 5-bromo-2’-deoxyuridine assay and isolated mice lungs, respectively. Results: Our results revealed that Yarsagumba extract and its bioactive compound cordycepin significantly attenuated the proliferation of human pulmonary artery smooth muscle cells derived from donor and PH subjects. In isolated murine lungs, only Yarsagumba extract, but not cordycepin, resulted in vasodilatation, indicating the probable existence of other bioactive metabolites present in Yarsagumba that may be responsible for this outcome. Conclusion: Future comprehensive in vivo and in vitro research is crucially needed to discover the profound mechanistic insights with regard to this promising therapeutic potency of Yarsagumba extract and to provide further evidence as to whether it can be used as a strategy for the treatment of PH.